ЯЗЫК И КУЛЬТУРА – КAК СИСТЕМА КОММУНИКАЦИИ - Абдуллаева Р.A. (SCIENCE and SOCIETY, 2023)
This article examines the language as a social phenomenon. It cannot be mastered outside of social interaction, i.e. without communicating with other people. Although the process of socialization is largely based on the imitation of gestures - nodding, manners of smiling and frowning - language serves as the main means of transmitting culture.